Series of Digital Based Material as Innovation for Marine and Fisheries Education Learning Media - Ahmad Satibi; Daniel Julianto Tarigan; Andre Aprinaldo; Ahmad Beryliumsyah Ikmaludin; Wildan Aprizal Arifin; Hari Din Nugraha (INVOTEC, 2022)
Smartphone users are increasing every year. This increase is due to the functions of smartphone technology, which help a lot to meet the needs of the community, social media, entertainment, shopping, work, managing finances, health and education. This must be anticipated by increasing digital-based educational content to optimise opportunities for improving technology to accelerate the quality of education. The development of learning materials in digital form is arranged in an android-based application.  Innovative use of information and communication technology (ICT) to support marine and fishing learning strategy lectures in the form of application breakthroughs to optimise learning. This research aims to make learning media innovations related to the marine and  fishinglearning strategy lecture process. This study uses the DBR (Design-Based Research) method in the form of qualitative data collection and descriptive analysis. Data collection was carried out in a mixed manner, namely by providing direct and indirect questionnaires, then quantitatively processing them using the DBR approach. The results of this research are an Android-based learning media innovation with information on marine and fisheries learning strategy lecture material that is packaged as attractively as possible and has a user-friendly display to make it easier to use.